Re-assessing the Design Needs of Trans-Radial Amputees in Product Design Innovation - Muhammad Jameel Mohamed Kamil; Sarah Moi Li Shi; Mohd Najib Abdullah Sani (Wacana Seni Journal of Arts Discourse, 2020)
The previous study on design for disabled people has indicates that product development for trans-radial amputees should integrate designer’s reflection in identifying significant variables such as the real needs of their users, functionality, ergonomic aspect, and aesthetic. Hence, this paper intends to re-assess the design needs of trans-radial amputees through an observation study with 15 trans-radial amputees (right side). The observation aims to understand the difficulties that occurred in the daily activities of amputees, in their home situation without the help of prosthesis. The result of the study suggests the amputees’ main struggle in their daily activities; preparing meals and eating independently. Therefore, a few design criteria have been proposed, and the prototype design was successfully developed as a proposal for potential future development and production. It is hoped the outcome of this research help to surpass the kind of device constrained to help amputees preparing meals and eating independently.